2016
DOI: 10.1007/s10290-016-0255-z
|View full text |Cite
|
Sign up to set email alerts
|

Foreign direct investment and firm performance: an empirical analysis of Italian firms

Abstract: Both empirical and theoretical literature show that multinational firms exhibit a competitive advantage before investing abroad. However, there are no clear empirical results regarding the ex post effects of foreign direct investment (FDI) on firm performance, partially due to the inadequacy of available firmlevel data. We build a brand new firm-level dataset able both to represent the extent of Italian firms' foreign activity and to provide reliable measures of key performance indicators, especially total fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(38 citation statements)
references
References 65 publications
3
35
0
Order By: Relevance
“…From ORBIS, we construct a sample of worldwide manufacturing affiliate firms that are majority owned by a European parent company whose main sector is a manufacturing industry. Papers that have used similar information to examine FDI activity include, among others, Geishecker et al (2009), Chen and Moore (2010), Engel, Procher, and Schmidt (2013), Mart ı et al (2015), Damijan et al (2016) and Borin and Mancini (2016). To determine whether an investment can be considered FDI, the OECD (2005) recommends classifying an enterprise within a country on the basis of the presence or absence of effective foreign participation in its capital.…”
Section: Data and Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…From ORBIS, we construct a sample of worldwide manufacturing affiliate firms that are majority owned by a European parent company whose main sector is a manufacturing industry. Papers that have used similar information to examine FDI activity include, among others, Geishecker et al (2009), Chen and Moore (2010), Engel, Procher, and Schmidt (2013), Mart ı et al (2015), Damijan et al (2016) and Borin and Mancini (2016). To determine whether an investment can be considered FDI, the OECD (2005) recommends classifying an enterprise within a country on the basis of the presence or absence of effective foreign participation in its capital.…”
Section: Data and Measurementmentioning
confidence: 99%
“…(), Damijan et al. () and Borin and Mancini (). To determine whether an investment can be considered FDI, the OECD () recommends classifying an enterprise within a country on the basis of the presence or absence of effective foreign participation in its capital.…”
Section: Data and Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Firms are initially divided into a non-CAT and an CAT group, taking due account of multinationals (MNE), which are over-represented among CAT firms and have been shown to be among the most efficient companies (see Borin and Mancini, 2015, for a quantification of the productivity premium of Italian multinationals). Firms are then allocated to the following subgroups depending on their status: (1) non-MNE non-CAT firms, (2) non-MNE CAT firms, (3) MNE non-CAT, and (4) MNE and CAT.…”
Section: Cat Firms Do It Bettermentioning
confidence: 99%
“…They found that the link between companies investments in R&D and labour productivity in micro sized companies does not differ largely from larger ones. In another study, Borin and Mancini (2016) measured the effects of foreign direct investment on the performance of Italian companies. They found an effect on the growth rate of labour productivity only in short time horizons and pointed out the importance of the given type of economic sector.…”
Section: Introductionmentioning
confidence: 99%